Coronavirus Disease Stress Among Italian Healthcare Workers: The Role of Coping Humor - Canestrari, Carla; Bongelli, Ramona; Fermani, Alessandra; Riccioni, Ilaria; Bertolazzi, Alessia; Muzi, Morena; Burro, Roberto (Frontiers in Psychology, 2021)
The study aimed to understand how coping strategies in general and humor-based coping strategies in particular modulate the perception of pandemic-related stress in a sample of Italian healthcare workers during the COVID-19 outbreak in Italy. A total of 625 healthcare workers anonymously and voluntarily completed a 10-minute questionnaire, which included psychometrically valid measurements preceded by a set of questions aimed at determining workers’ exposure to COVID-19. The Perceived Stress Scale was used to measure healthcare workers’ stress levels, and the Brief COPE Scale and Coping Humor Scale were used to assess participants’ avoidant or approach coping style and verify the degree to which they relied on humor to cope with stress. The results show that 1) levels of perceived stress were higher in healthcare workers who were more exposed to COVID-19 (i.e., who came into contact with COVID-19 patients or worked in wards dedicated to COVID-19) in comparison to less-exposed workers; 2) participants who reported a higher use of avoidant coping strategies perceived the situation as more stressful than those who used them less; 3) healthcare workers who reported higher use of humor-based coping strategies perceived the situation as less stressful in comparison with those who reported less use of coping humor. Such findings expanded other research studies by including coping humor as a potential factor to mitigate the perceived stress related to COVID-19. The paper concludes with a discussion of implications for future research and limitations of the study.